Pola Komunikasi Guru dalam Interaksi dengan Anak Autism Spectrum Disorder (ASD) - Istiqomah Maharani Pasiori; Pasiori, Istiqomah Maharani; Erina Pricilia Ananta; Setia Widyaddini (CV. Causalita Dynamic Solutions, 2025)
This study aims to systematically examine the communication patterns used by teachers in interacting with autistic children, as well as the factors that influence the effectiveness of this communication in the educational environment. The method used was Systematic Literature Review (SLR) of 15 scientific articles published between 2020 and 2025. The results were classified into five main themes, the findings showed that teachers use verbal and nonverbal communication, with strategies such as PECS, ABA, DTT, and interpersonal communication based on empathy and emotional support. However, one-way communication and limited facilities are still an obstacle. The role of parents and teacher training also proved influential in supporting effective communication. This study confirms the importance of an individualized approach, collaborative environmental support and increased teacher capacity to create inclusive learning that is responsive to the needs of children with autism